Sustained Aftereffect of α-tACS Lasts Up to 70 min after Stimulation - Kasten, Florian H.; Dowsett, James; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2016)
Transcranial alternating current stimulation (tACS) has been repeatedly demonstrated to increase power of endogenous brain oscillations in the range of the stimulated frequency after stimulation. In the alpha band this aftereffect has been shown to persist for at least 30 minutes. However, in most experiments the aftereffect exceeded the duration of the measurement. Thus, it remains unclear how the effect develops beyond these 30 minutes and when it decays. The current study aimed to extend existing findings by monitoring the physiological aftereffect of tACS in the alpha range for an extended period of 90 minutes post-stimulation. To this end participants received either 20 minutes of tACS or sham stimulation with intensities below their individual sensation threshold at the individual alpha frequency. Electroencephalogram was acquired during 3 minutes before and ninety minutes after stimulation. Subjects performed a visual vigilance task during the whole measurement. While the enhanced power in the individual alpha band did not return back to pre-stimulation baseline in the stimulation group, the difference between stimulation and sham diminishes after 70 minutes due to a natural alpha increase of the sham group.